Characteristics of and Factors Affecting Foreign Direct Investment in the Malaysian Furniture Industry - Saadun, Norzanalia (2007)
This study was undertaken to asses the characteristics of foreign direct investment (FDI) in the Malaysian furniture industry. This study answered three specific objectives namely, to evaluate the characteristics of FDI in the Malaysian furniture industry from 1985-2004, to compare the characteristics of FDI in the Malaysian furniture industry during first Industrial Master Plan (IMP) (1986-1995) and second IMP (1996-2004), and lastly to determine the factors affecting FDI in the Malaysian furniture industry. Secondary published data on furniture investments were collected from the Malaysian Industrial ~ e v e l o ~meAn tu thority (MIDA). The value of investments were deflated by the Malaysian consumer price index (CPI) obtained from the International Financial Statistics (IFS, 64), published by the International Monetary Fund (IMF), whereby the year 2000 was treated as the base year (2000=100). Descriptive analyses were employed in order to analyse the trend of investment according to the period of study identified in the research objectives. The study was then followed by questionnaire survey and open-ended interviews of identified foreign manufacturing companies. Rank order analysis was applied to rank the locational factors affecting the decision of FDI in the Malaysian furniture industry. The results showed that from 1985 to 2004, investment in the Malaysian furniture manufacturing had mixed performance from both domestic and foreign sources of investment. Of the 661 projects approved for establishment, 340 projects or 51 percent were accounted from foreign investment. Throughout the period of study, the capital ownership was controlled by domestic investment with 63 percent share of the total real equity. On the other hand, in terms of ownership equity, the foreign investment had better control, having 53 percent of total real equity. With respect to fixed assets investment, the domestic investors were much more aggressive in purchasing and acquiring fixed assets. In terms of employment opportunities, foreign projects had provided 50,219 employments or 53 percent share of the total 9 1,O 19 employments in the furniture manufacturing projects. Over the period of study, furniture manufacturing projects have been found to be more capital-intensive and less labour-intensive a shown by the increased of capital investment per employee (CIPE) ratio. The major sources of FDI in the Malaysian furniture industry, for the past 20 years were from Taiwan, Singapore and Japan. The results on the comparison of the investment in the Malaysian furniture industry between two IMP periods showed a declining trend of foreign investment during the second IMP period. The domestic investment in the furniture manufacturing however continued to be on a positive trend. This suggested that the foreign furniture manufacturer is in the stage of consolidation. In terms of CIPE ratio, although there had been an increasing trend during the second IMP period, however the foreign furniture projects were still below the RM55,OOO threshold set by the government. This indicates that foreign furniture projects was still labour-intensive in nature. Despite of decreased value of investment fiom the major sources of FDI in the Malaysian fbrniture industry during the second IMP period, however new sources of investment from other country during the second IMP showed that the Malaysian furniture industry is still attractive for foreign investors. Hence, the new structured policy must provide competitiveness in terms of cost, as new locations in Southeast Asia are available. The survey analysis concluded that the stability of the government, investment guarantee agreement with the country, freedom to remit earning and interest royalties, freedom to repatriate capital, availability of skilled labour force, prevalence of peaceful industrial relations, reliable supply of power, water and gas, transportation and communication facilities, support of banking and insurance services, external demand and export market potential, tariff and trade protection, tax incentives, efficiency of public sector, economic stability and exchange rate stability are the most important factors affecting FDI in the Malaysian furniture industry. The analysis on traditional economic determinants of FDI such as low cost labour and availability of raw material had showed that these factors were less important while skilled labour was decisive in affecting FDI in the Malaysian firniture industry. Therefore, effective training especially from local training institutions has to be intensified in order to produce a well-educated and skilled work-force for the industry.